2016
DOI: 10.3762/bjnano.7.97
|View full text |Cite
|
Sign up to set email alerts
|

NO gas sensing at room temperature using single titanium oxide nanodot sensors created by atomic force microscopy nanolithography

Abstract: SummaryIn this work, the fabrication of single titanium oxide nanodot (ND) resistive sensors for NO gas sensing at room temperature is reported. Two atomic force microscopy nanolithography methods, nanomachining and nano-oxidation, are employed. A single titanium nanowire (NW) is created first along with contact electrodes and a single titanium oxide ND is subsequently produced in the NW. Gas sensing is realized by the photo-activation and the photo-recovery approaches. It is found that a sensor with a smaller… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 38 publications
0
4
0
1
Order By: Relevance
“…2. Room temperature gas sensors based on single phase semiconducting metal oxide nanostructures 2.1 N-type semiconducting metal oxide nanostructures and gas sensors N-type SMONs are the most reported sensing materials for RT resistive gas sensors, and they include ZnO, [152][153][154][155][156] SnO 2 , [157][158][159][160] In 2 O 3 , 161 WO 3 , 162 TiO 2 , [163][164][165][166] Fe 2 O 3 , [167][168][169] MoO 3 , 170 174 acetone, 175 alcohol, 106 HCHO, 176 liquefied petroleum gas (LPG), etc. Table 1 summarizes some of the reported RT sensors using the n-type SMONs.…”
Section: Yongqing Fumentioning
confidence: 99%
“…2. Room temperature gas sensors based on single phase semiconducting metal oxide nanostructures 2.1 N-type semiconducting metal oxide nanostructures and gas sensors N-type SMONs are the most reported sensing materials for RT resistive gas sensors, and they include ZnO, [152][153][154][155][156] SnO 2 , [157][158][159][160] In 2 O 3 , 161 WO 3 , 162 TiO 2 , [163][164][165][166] Fe 2 O 3 , [167][168][169] MoO 3 , 170 174 acetone, 175 alcohol, 106 HCHO, 176 liquefied petroleum gas (LPG), etc. Table 1 summarizes some of the reported RT sensors using the n-type SMONs.…”
Section: Yongqing Fumentioning
confidence: 99%
“…Moreover, it was found that the average response and recovery time of the TSV-structured TiO 2 NO gas sensor are about 109 and 144 s. The response and recovery time are defined as the time required for a 90% change in the signal. Furthermore, this result indicated that the TSV-structured TiO 2 NO gas sensor had a better response and recovery time than the previous studies [36][37][38][39][40], as shown in Table 1.…”
Section: Resultsmentioning
confidence: 65%
“…During printing, the metal electrodes are precisely placed on top of the 1D structures. However, all these fabrication techniques are still in a preliminary stage of development, despite some promising results that have recently been reported [254][255][256][257][258][259][260][261]. advantage of this technique is its flexibility due to direct recording capabilities without using any masks [237,240].…”
Section: Features Of the Fabrication Of Gas Sensors Based On Individumentioning
confidence: 99%
“…During printing, the metal electrodes are precisely placed on top of the 1D structures. However, all these fabrication techniques are still in a preliminary stage of development, despite some promising results that have recently been reported [ 254 , 255 , 256 , 257 , 258 , 259 , 260 , 261 ].…”
Section: 1d Structuresmentioning
confidence: 99%